Scepticism in the History of Philosophy
XXII, 294 p.
Keywords: Scepticism in the History of Philosophy is a dialogue between leading Latin American and North American scholars concerned with the history of scepticism from ancient times to present day philosophy. The volume contains interesting discussions by a wide range of philosophers and historians of philosophy. The book should be of great interest to many philosophers who are interested in scepticism. It is unique in presenting in English the work of philosophers from Mexico, Brazil, Argentina and Chile; philosophers not well known to the English speaking world.